The Effect Of Kinetic Exercises Using The Analogous Method To Improve The Performance Of The Motor Chain On The Ground Movement Mat For Fifth Grade Students - Ahmed Okab Al-Huseeinawi, Nadihm (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to prepare kinetic exercises and their effect on improving the performance of the kinematic chain on the mat of ground movements using the method of learning with analogies, as the null hypothesis was developed that there were no statistically significant differences for the research groups, as the researcher used the experimental method for its suitability to solve the research problem and the design of the two equivalent groups with the test was chosen The pre- and post-test are randomly selected, and the research sample includes the fifth grade pupils, whose number is 40 students, and they were divided into two control and experimental groups, each group (20) students, and the researcher conducted the pre-test and prepared kinetic exercises bearing the characteristic of sequential performance and the rhythm and compatibility close to the performance of the series, within Learning time to perform the series in the weekly plan and for six units, where the exercises were explained and applied in the second five minutes of warm-up and also in the main section at the beginning of learning with teaching the series because its performance is easier than connecting the vocabulary of the series and after acquiring the nature of the coherent performance that achieved the ease of performing the series and the researcher used devices And with the appropriate tools, the researcher conducted the post test, and the researcher reached the following conclusions: The performance of the kinesthetic exercises achieved the best performance of the kinetic chain by developing the kinetic rhythm in the process of linking the movements that make up the chain and the accuracy of the kinematic transmission and compatibility, and that the use of the sequential kinematic exercises using the learning method with analogies to learn the performance of the chain reduced the learning time and the preference for using these ages from exercises with separate performance.